Uma abordagem para a construção de triângulos e do Teorema de Pitágoras mediada pelo software SuperLogo - Gonçalves, Mariana Dias (2014)
This study aims to analyze a sequence of activities for students of the 8th grade of Elementary School II mediated by the use of SuperLogo software. This teaching sequence has been proposed to develop students‟ learning of the Pythagorean theorem by geometric constructions in the search of a knowledge grounded in reflection, not in the repetition. Preliminary studies, from the literature review, allowed the elaboration of the following research question: How does the development of an educational strategy based on the creation of didactic situations, using the SuperLogo software, can contribute to building meaningful learning related to geometric constructions? The proposed research, a qualitative study, has considered the Theory of Didactical Situations and the conception of didactic contract, both authored by Brousseau (1997), and Theory of Meaningful Learning of Ausubel (2002). With regard to the technological support, have been studied works of Oliveira (2013), Levy (1993), Borba and Villarreal (2005) and Tikhomirov (1981). The analysis of the protocols and discussions of the subjects during the field survey revealed that the proposed activities provoked thoughts about some topics in plane geometry, and permitted the discovery and consolidation of the Pythagorean Theorem. This experiment revealed the advantage of the approach taken towards the construction of a meaningful learning from a new configuration of the didactic contract, rather than the reproduction of routes in teaching geometric constructions